ANALISA KINERJA KEUANGAN TERHADAP PREDIKSI FINANCIAL DISTRESS UKURAN PERUSAHAAN SEBAGAI VARIABEL KONTROL - Faradila, Putri; Aziz, Alfida (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2016)
This study was conducted to examine the effect of financial performance asmeasured by the variable Current Ratio, Net Profit Margin, Debt Ratio of Financial Distress prediction. This study uses a control variable is Firm Size. The population in this study were 142 companies listed in Indonesia Stock Exchange year 2013. This study used a sample amounted to 78 companies listed on the Indonesia Stock Exchange that have been adapted to the criteria of the study sample. By using purposive sampling method consists of 64 companies non-financial distress and 14 companies financial distress. Criteria for financial distress in this study was measured by using the interest coverage ratio. Data were tested using logistic regression method with a confidence level of 5%. The results showed that the variable Current Ratio and Debt Ratio are not effect on the Financial Distress prediction. Firm size variable as control variable is also not effect on the Financial Distress prediction. The results showed that the only variable Net Profit Margin which influence of Financial Distress prediction.